Banking on the church: thoughts on re-infusing virtues into church culture and leadership in response to clergy sexual abuse - Driscoll, Cathy (Journal of management, spirituality & religion, 2018)
We provide a cross-disciplinary and cross-contextual analysis to explore comparisons between the church and big banks regarding leader power structures, response to moral failure, relationships with members/stakeholders, and resistance to structural change. Although we largely focus on the context of clergy sexual abuse, we show how perceived uniqueness of individuals and institutions (whether in banks or churches) has been used to thwart the potential for improved understanding of moral failures across organizations and institutions. We provide a discussion and implications for church leaders in the context of a virtues-infused organizational culture. We also discuss what non-religious organizations, such as banks, and their leaders can learn about these issues from what we believe is distinct about the church as a spirit-infused and virtues-infused entity. We conclude with some key areas for future reflection and research.